Associations Between Symptoms of Depression and Air Pollutant Exposure Among Older Adults: Results From the Taiwan Longitudinal Study on Aging (TLSA) - Wang, Kuan-Chin; Lo, Yuan-Ting C.; Liao, Chun-Cheng; Jou, Yann-Yuh; Huang, Han-Bin (Frontiers in Public Health, 2022)
Background: Little epidemiological research has investigated the associations of air pollutant exposure over various time windows with older adults’ symptoms of depression. This study aimed to analyze the relationships of long- and short-term ambient air pollution exposure (to coarse particulate matter, O3, SO2, CO, and NOx) with depressive symptoms in a sample of community-dwelling older adults. Methods: A sample of older adults (n = 1956) was recruited from a nationally representative multiple-wave study (Taiwan Longitudinal Study on Aging). Between 1996 and 2007, four waves of surveys investigated depressive symptoms by using the 10-item Center for Epidemiologic Studies Depression questionnaire. We approximated air pollutant concentrations from 1995 to 2007 by using daily concentration data for five air pollutants at air quality monitoring stations in the administrative zone of participants’ residences. after adjusting for covariates, we applied generalized linear mixed models to analyze associations for different exposure windows (7-, 14-, 21-, 30-, 60-, 90-, and 180-day and 1-year moving averages). Results: In a one-pollutant model, long- and short-term exposure to CO and NOx was associated with heightened risks of depressive symptoms; the odds ratio and corresponding 95% confidence interval for each interquartile range (IQR) increment in CO at 7-, 14-, 21-, 30-, 60-, 90-, and 180-day and 1-year moving averages were 1.232 (1.16, 1.361), 1.237 (1.136, 1.348), 1.216 (1.128, 1.311), 1.231 (1.13, 1.338), 1.224 (1.124, 1.332), 1.192 (1.106, 1.285), 1.228 (1.122, 1.344), and 1.180 (1.102, 1.265), respectively. Those for each IQR increment in NOx were 1.312 (1.158, 1.488), 1.274 (1.162, 1.398), 1.346 (1.154, 1.570), 1.310 (1.186, 1.447), 1.345 (1.209, 1.496), 1.348 (1.210, 1.501), 1.324 (1.192, 1.471), and 1.219 (1.130, 1.314), respectively. The exposure to PM10, O3, and SO2 over various windows were not significant. The In the two-pollutant model, only the associations of NOx exposure with depressive symptoms remained robust after adjustment for any other pollutant. Conclusions: Exposure to traffic-associated air pollutants could increase depression risks among older adults.